Mediation and Sulh as an Alternative to Litigation: A Study of the Syariah and Civil Courts Practices in Malaysia - Hendun Abd Rahman Shah; Mustafa ‘afifi Ab. Halim; Norfadhilah Mohamad Ali (Darulfunun Ilahiyat)
Malaysia is a country that practices a dual legal system in which the family matters of Muslims fall within the jurisdiction of the Syariah Court. Majlis Sulh (Mediation Council) is a form of alternative dispute resolution (ADR) used by the Syariah court to reduce the backlog of cases in the courts. Meanwhile, the Court Mediation Centre is the avenue for nonmuslims to resolve their family disputes amicably. Here, mediation is not limited to family matters; it is also applicable in other disputes, including traffic accidents and contract cases. Mediation involves low costs, short timeframes, and informal processes compared to litigation. Mediation has now become a part of the procedures in certain courts. This paper aims to examine and compare the mediation practices in Syariah and civil courts in Malaysia using qualitative methodology and library-based research by reviewing scholarly literature, analysing legal documents and seeking expert views. This will be followed by an analysis of the comparison of court-annexed mediation practices, with emphasis on the process, procedures, scope, jurisdiction, and challenges. The paper then offers suggestions on how some challenges in implementing court mediation methods can be overcome. Finally, the findings of the study show that there are differences in the mediation practices and challenges in these two courts, but the best practices can be adopted to improve the process and practice of mediation in the courts.